The Three Stands of Innovation : An Interview with Jean-François Richard - Liounis, Audrey (2012)
In his 2002 book, High Noon, economist and former World Bank vice president Jean Francois Rischard stressed that in order to address urgent, global issues, the world nedded "imagination and a different type of thinking"-and needed it within two decades, not five or ten.